Reparação do dano à imagem das pessoas jurídicas - Costa, Deborah Regina Lambach Ferreira da (2010)
In a globalized world, owners of image rights are more vulnerable to damages for which compensation may be sought. New technologies, the web, TV, broadcasting channels and mechanical systems in general, which disseminate information in real time making it accessible to millions of people, increase this exposure to defamation. Both legal entities governed by private and public law that own rights of publicity consistent with their legal status run the risk of having their images damaged. Items V and X of article 5 of the Brazilian Constitution provide that these entities are entitle to compensation for libel and slander, or moral damages in a literal translation from Portuguese. Detaching the concept of libel and slander from pain and suffering , the Brazilian Superior Court of Justice published case law summary [ Súmula ] No. 227 which resulted in the application of article 10 of the European Convention on Human Rights to prevent abuse of the freedom of expression and ensure maximum protection to reputation. This study is an in-depth analysis of image rights based on the initial assumption that these are autonomous rights of publicity entitled to protection both at constitutional and infraconstitutional level. The compensation for image damages leaves formal positivism aside to follow the paradigm shift introduced by the Constitution of Brazil ratified in 1988 when social, ethical and operational principles -- even within the scope of civil liability -- where brought to light allowing the interpretation of the Civil Code to be consistent with the concepts of equity and justice in an attempt to foster ethics and compassion in society